Productive Entry Pathways of Human Rhinoviruses - Renate Fuchs; Dieter Blaas (Advances in Virology)
Currently, complete or partial genome sequences of more than 150 human rhinovirus (HRV) isolates are known. Twelve species A use members of the low-density lipoprotein receptor family for cell entry, whereas the remaining HRV-A and all HRV-B bind ICAM-1. HRV-Cs exploit an unknown receptor. At least all A and B type viruses depend on receptor-mediated endocytosis for infection. In HeLa cells, they are internalized mainly by a clathrin- and dynamin-dependent mechanism. Upon uptake into acidic compartments, the icosahedral HRV capsid expands by ~4% and holes open at the 2-fold axes, close to the pseudo-3-fold axes and at the base of the star-shaped dome protruding at the vertices. RNA-protein interactions are broken and new ones are established, the small internal myristoylated capsid protein VP4 is expelled, and amphipathic N-terminal sequences of VP1 become exposed. The now hydrophobic subviral particle attaches to the inner surface of endosomes and transfers its genomic (+) ssRNA into the cytosol. The RNA leaves the virus starting with the poly(A) tail at its 3′-end and passes through a membrane pore contiguous with one of the holes in the capsid wall. Alternatively, the endosome is disrupted and the RNA freely diffuses into the cytoplasm.